Stimulasi Bermain Bercerita Metode Flanel Meningkatkan Sosialisasi Pada Anak Usia Prasekolah - Hindyah Ike Suhariati (coba, 2016)
Socialization is an ability that pre-school children must have in order to build good interaction with their friends in school. In fact 70% of pre-school children yet unable to make socialization in school. The purpose of this study is explaining the influence of flannel story telling play stimulation method to the socialization of pre school children. The design of this study is Quasi Experiment. All of the pre-school children that experiencing lack of socialization in TK. Dharma Wanita Persatuan RSJ Dr. Radjiman Wediodiningrat Lawang become the population. Non Randomise Sampling method is used, with 32 respondent, 16 children used as treatment group and 16 others as the control group. The independent variable was flannel story telling play stimulation method and the dependent variable was the socialization. Data was analized by Wilcoxon Sign Rank test and Mann-Whitney test with significance rate 95% (α = 0,05). The result showed that flannel story socialization improvement (p = 0,000), playing activity according to the curriculum didn’t improve the pre-school children socialization significantly (p = 0,157), there are difference between control group and after treatment group socialization with Mann-Whitney test (p = 0,004). Flannel story telling play stimulation method could improve socialization ability of telling play stimulation method influences the pre-school childrens pre-school children significantly. This playing activity can be used as the pediatric nursing care cast, to treat children with socialization problems. Keywords : Flannel playing method, Socialization, pre-school